Relationship between the Municipal Human Development Index and Basic Sanitation (Research, Society and Development, 2022)
Law No. 14,026/2020 establishes the importance of information and sanitation indicators, and also defines information systems as an instrument to promote “transparency of actions”, so necessary for the elaboration of strategies and actions in that sector. The general objective of the article was to relate basic sanitation with a focus on water supply and sanitation with the human development index in Brazilian municipalities. Through the specific objectives: obtain and analyze municipal human development indicators (IDHM) in Brazilian municipalities; obtain and analyze the indicators of collection, removal and treatment of sanitary sewage, as well as the level of drinking water service in Brazilian municipalities and relate the MHDI indicators with the indicators of water supply and sanitary sewage. For this, a qualitative research was carried out through a bibliographic survey. In fact, in the light of the aforementioned legislation, the municipalities that participated in the survey of the National Sanitation Information System were analyzed through the Diagnosis of Water and Sewerage Services and also with information regarding adequate sewage from the National Research on Sanitation. As a result, information from the municipalities themselves was used, when they carried out the water and sewage treatment actions. Based on this work, the IDHM of the referred municipalities were listed and the results were presented through graphs and charts.